2021
DOI: 10.1186/s13045-021-01213-z
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national cancer incidence and death for 29 cancer groups in 2019 and trends analysis of the global cancer burden, 1990–2019

Abstract: Background and aims Cancer will soon become the leading cause of death in every country in the twenty-first century. This study aimed to analyze the mortality and morbidity of 29 types of cancer in 204 countries or regions from 1990 to 2019 to guide global cancer prevention and control. Methods Detailed information for 29 cancer groups was collected from the Global Burden of Disease Study in 2019. The age-standardized incidence rate (ASIR) and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 69 publications
1
102
0
1
Order By: Relevance
“…They posit that occupational exposures may be causing these relationships in men. Since 1990, the number of people dying from cancer has doubled, rising to 10 million across the globe [ 84 ]. In 2019, Western Europe had one of the highest number of cancer deaths across the globe (1.27 million) and the highest incidences along with North America and East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…They posit that occupational exposures may be causing these relationships in men. Since 1990, the number of people dying from cancer has doubled, rising to 10 million across the globe [ 84 ]. In 2019, Western Europe had one of the highest number of cancer deaths across the globe (1.27 million) and the highest incidences along with North America and East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a serious chronic disease which becomes the key causes of death and disability in the world. An analysis of the global burden of cancer 1990–2019 showed that more than 10 million people died of cancer in 2019, roughly double the number in 1990 ( Lin et al, 2021 ). Using data updated in 2020 from the International Agency for Research on Cancer, it is estimated that there are 19.3 million new cancer cases and nearly 10 million cancer patients’ death worldwide in 2020 ( Sung et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CM arises from the malignant transformation of melanocytes found in the skin epidermis, which produce the photoprotective pigment melanin and are also involved in ROS/RNS scavenging, thermoregulation and immunomodulation ( 2 4 ). Even though it only represents 5% of all types of skin neoplasms, CM is considered the most lethal, being responsible for 60-75% of skin cancer-related deaths ( 5 7 ). From 1990 to 2019, incident cases of CM have increased by 170% worldwide, faster than most neoplasms, mainly due to a rapidly aging population, changes in lifestyle and better screening ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%